Health and disability pension -- an intersection of disease, psychosocial stress and gender. Long term follow up of persons with impairment of the loco motor system. - Kaiser P; Mattsson B; Marklund S; Wimo A (Work, 2008)
OBJECTIVES: To evaluate the outcome after 1, 2, 3 and 10 years of rehabilitation conducted by the Swedish Social Insurance Office, in relation to socioeconomic, psychosocial and gender aspects. STUDY DESIGN: A retro and prospective study of 372 individuals rehabilitated by the National Swedish Insurance Office 1993-1994. Diagnosis, socio demographic data, Sense of Coherence and Perceived Health were compared with register data in terms of sickness benefit and disability pension up to 10 years. RESULTS: At the 10 year follow up 52% of the men and 57% of the women were granted any kind of DP. 82% of the men with low PH and women with a PM or a low PH had any kind of benefit 10 year after rehabilitation started. High age and low PH increases the risk of a full DP after 3 as well as 10 years for both men and women. At the 3 year follow up however, low education was also important for a full DP for men and having a Psychosocial Marker for women. The factors civil status and kind of profession did not significantly relate to a full DP after 10 year. CONCLUSIONS: In different ways factors as age, education, psychosocial stress, Sense of Coherence and Perceived Health mediate the rehabilitation process in significant ways by affecting the manifestation of the disease itself and/or via the context in which the rehabilitation takes place, in combination with individual factors that acts over a long time. Age and Perceived Health seems to be the most important factors of them all.